Biodegradation of Oil-Based Plastic Wastes by Bacteria Isolated from Fish Breeding Tanks - Al-Imara, Eman A.; Al-Mayyahi, Baqer A.; Al-Ankush, Mujtaba A. T.; Al- Shatty, Sabah M. (Iraqi Journal of Science, 2023)
Several studies have shown that certain microbes, mainly bacteria may have the ability to digest plastic wastes. The goal of this study was to see how well Bacillus subtilis, Staphylococcus lentus, Aeromonas hydrophila, Sphingomonas paucimobilis and Kocuria paedia degrade three kinds of oil-based plastics: low-density polyethylene (LDPE), polystyrene (PS) and polyvinylchloride (PVC) polymer sheets. The experiment was conducted for 30 days under laboratory conditions with occasional shaking at 180 rpm and 32°C. Biodegradation was measured in terms of weight loss.. Accordingto IR Spectroscopy, the C-H stretch band at 2920cm-1 improved as a result of bacterial degradation of polyethylene. The most affected polymers were LDPE and PVC films. While PS films were the least affected polymers. B. subtilis was shown to be the most successful of the five bacterial species, whereas K. paedia was determined to be the least effective.